(untitled) (Journal of Research Updates in Polymer Science, 2017)
The incorporation of recycled polymers from waste latex paints (WLPs) in concrete manufacturing is very limited. In fact, this practice cannot be formally implemented without thorough assessment of the various implications that could result from WLP additions on concrete properties. This paper seeks to provide better understanding on effect of WLP constituents and substitution rates on concrete fresh and mechanical properties. It also examines the effect of incorporating naphthalene-based high-range water reducer (HRWR) to mitigate the detrimental effects associated with such additions. Tested WLPs were not randomly collected from waste collection sites; rather produced to assure full traceability of composition and then stored for around 1-year to expire. Test results have shown that workability, setting time, and hardened properties of concrete are directly affected by the polymer latex type and content including the pigment/extender ratio. The use of HRWR is efficient to control work ability and its loss over time when WLPs are disposed in concrete at relatively high rate of 10% of mixing water. The incorporation of HRWR should be coupled with certain reduction in free water to control the drop in compressive strength and bond to embedded steel bars.